Impacts of an Early Stage Education Intervention on Students' Learning Achievement : Evidence from the Philippines - Yamauchi, Futoshi; Liu, Yanyan (Taylor and Francis, 2013)
This article examines the impact of a large supply-side education intervention in the Philippines, the Third Elementary Education Project, on students' national achievement test scores. We find that two years' exposure to the programme significantly increased test scores at grades 4 to 6 by about 4.5 to 5 score points. Interestingly, the mathematics score was more responsive to this education reform than other subjects. We also find that textbooks, instructional training of teachers and new classroom constructions particularly contributed to these outcomes. The empirical results also imply that early stage investments improve student performance at later stages in the elementary school cycle, which suggests that social returns to such an investment are greater than what the current study demonstrates.